UJI EFEK SEDATIF EKSTRAK n-HEKSAN DARI DAUN KRATOM (Mitragyna speciosa Korth.) PADA MENCIT JANTAN GALUR BALB/c - ., Anna Hidayati (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Insomnia is a sleep disorder that can cause a variety of serious health problemsrequiring treatment. The using of synthetic drugs have dangerous side effects than therapywhich is resulted. Therefore, alternative treatments which derived from natural such askratom leaves are needed. The purpose of this study is to know the sedative effect of nhexaneextract, the group of secondary metabolites, the effective dosage of n-hexaneextract of kratom leaves in producing sedative effect and thepotential of the extract nhexaneif it compares with diazepam. Extracts is obtained by maceration and somephytochemical screenings are done. The study used 30 mices were divided into 6 groups.Diazepam is used as a control (+), vegetable oil as a control (-) and n-hexane extract withdosage 1 (24 mg/kgBW), dosage 2 (48 mg/kgBW), dosage 3 (72 mg/kgBW) and dosage4 (96 mg/kgBW) which is given by oral administration. Sedative effects experiment wasconducted by using the traction test and fireplate test. The observation was done both ofqualitative and quantitative ways. Qualitative data includes turning the body and corneawhile quantitative data includes time falling, turning the body and jumping. Quantitativedata was tested by statistic using One-way ANOVA Post Hoc Test (Tukey HSD andLSD) Kruskal Wallis or Mann-Whitney. The results showed that n-hexane extract hadsedative effect contained the compound group of alkaloids, glycosides, steroids andflavonoids. The dosage 4 (96 mg/kgBW) of n-hexane extract of kratom leaves gavesedative effects better than diazepam.Keywords: Insomnia, Sedatives, Kratom